Proteomic profile in Perna viridis after exposed to Prorocentrum lima, a dinoflagellate producing DSP toxins. (January 2015) - Huang, Lu; Zou, Ying; Weng, Hui-wen; Li, Hong-Ye; Liu, Jie-Sheng; Yang, Wei-Dong
Abstract: In the current study, we compared protein profiles in gills of Perna viridis after exposure to Prorocentrum lima, a dinoflagellate producing DSP toxins, and identified the differential abundances of protein spots using 2D-electrophoresis. After exposure to P. lima, the level of okadaic acid (a main component of DSP toxins) in gills of P. viridis significantly increased at 6 h, but mussels were all apparently healthy without death. Among the 28 identified protein spots by MALDI TOF/TOF-MS, 12 proteins were up-regulated and 16 were down-regulated in the P. lima -exposed mussels. These identified proteins were involved in various biological activities, such as metabolism, cytoskeleton, signal transduction, response to oxidative stress and detoxification. Taken together, our results indicated that the presence of P. lima caused DSP toxins accumulation in mussel gill, and might consequently induce cytoskeletonal disorganization, oxidative stress, a dysfunction in metabolism and ubiquitination/proteasome activity. Highlights: Response of mussel to toxicity of OA was explored using proteomic approach. The presence of Prorocentrum lima strongly enhanced OA accumulation in mussel gill. P. lima may induce cytoskeleton disorganization and oxidative stress in mussel. Our findings provide global information for early response to OA chronic exposure. Abstract : The presence of Prorocentrum lima caused DSP toxins accumulation in mussel gill, and might consequently induce cytoskeletonal disorganization, a dysfunction in metabolism and proteasome activity.